Effect of Pre-Treatment on the Morphology and Chemical Properties of Polyethylene Terephthalate (PET)/Pineapple Leaf Fiber (PALF) Electrospun Mat - N Surip, S; M A Aziz, F; H Yuwono, A; Sofyan, N (International Journal of Engineering and Technology, 2019)
In the past decades, conventional petroleum-based plastics have resulted in environmental and sustainability issues. Thus, there has been significant interest in the utilization of natural materials for nanofibers product such as for filtration media.Â However, poor compatibility exists between polymers and natural fibers due to natural fibers hydrophilic properties leading to poor nanofibers formation. In this study, Pineapple Leaf Fiber (PALF) remarkable properties were explored. PALF undergo alkaline treatment and bleaching treatment in order to improve its compatibility. Thermal, morphology and structural properties of PALF raw (PR), PALF after alkali treatments (PA) and PALF after alkali + bleaching treatment (PB) were studied. Further, all the samples were diluted using Trifluoroacetic Acid (TFA) as the solvent and Polyethylene Terephthalate (PET) as the polymer carrier and proceed to electrospinning to produce a nanofibers electrospun mats. The electrospun mats were then characterized in terms of its chemical properties using Fourier transform infrared spectroscopy (FTIR) as well as the morphology which using Fields Emission Scanning Electron Microscopy (FESEM).Â FTIR result shows the electrospun PET does not produce any peak at 3400cm-1 due to its hydrophobic properties. Nevertheless, with addition of PALF, the peak was significantly increased. FESEM results indicated that the present of fibers led to a tendency of lower average fiber diameter compared to the neat PET. Unconnected and thin fibers were coexited from single fiber of PALF raw electrospun indicated that new fibers were ejected however the bond were collapsed during ejection thus did not produce a complete single fiber. Despite that, more uniform fibers of electrospun mat were produced by pre-treatment of PALF.Â